(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The concept of An Analytical Approaches On Sodium Aerosols For The Fast Reactor. Fast reactors were one of the first types of reactors built. New SFR designs have been created for the Generation IV Nuclear Energy Systems project. The goals of these new designs are to explore non-traditional applications of nuclear energy while developing new reactor designs that meet the demand for clean and reliable power generation and also focus on enhanced safety and the reduction of cost and proliferation risks. Many of these new reactor concepts involve reactors that use recycled fuels or metallic fuels, like the SFR